Women intimate partner violence revictimization during protection orders in Montevideo, Uruguay: risk factors and policy implications - Gambetta, Victoria (International journal of law, crime and justice, 2025)
This study explores risk factors for Protection Order (PO) violation in intimate partner violence (IPV) cases in Montevideo, Uruguay, a topic not yet investigated in Latin America. Using a sample of 1057 police-reported IPV cases, logistic regression compares literature-supported risk factors with those used in public policy to predict women's IPV revictimization. Results show that 26% of offenders violate POs, mainly through harassment (82%) and psychological violence (46%), and police monitoring reduces risk of offenders' recidivism by 48.5%. Additionally, they highlight that IPV trajectories of both victims (OR = 1.85) and offenders (OR = 1.89) are the strongest predictors of reabuse. These findings suggest that Uruguayan policymakers should rethink police intervention and public action on IPV by focusing on two key actions: increasing investment in data collection and analysis to improve PO monitoring and police response, and developing strategies beyond criminal sanctions to address offender treatment and victim support to prevent IPV reabuse.